Anti-aging plastic track material and preparation method thereof
The reaction of isophorone diisocyanate with modified polysiloxane and crown ether polymer, combined with zinc acetate solution, is solved by preparing anti-aging plastic runway materials, which short service life and risk of slipping and falling at night The problem has achieved the improvement of flame retardant, self-healing and fluorescence functions.
Patent Information
- Application Number
- CN202411444278.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing plastic runway materials have a short service life and are prone to slip and fall during night exercises, and are costly.
Isophorone diisocyanate, 1,3-propylene diamine and modified polysiloxane, and then mixed with crown ether polymer and zinc acetate solution to prepare anti-aging plastic runway materials, through flame retardant, self-healing and Fluorescence function improves material performance.
Improves the flame retardant performance, self-healing ability and fluorescence properties of the material, extends service life, reduces the risk of slipping at night, and reduces costs.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and specifically to an anti-aging plastic track material and a preparation method thereof. Background Art
[0002] With the progress of society and the advocacy of the country, people's demand for sports and fitness facilities is also increasing. The track, as a basic sports facility, has also experienced the stage from dirt track to cinder track and then to the current plastic track. Compared with dirt track and cinder track, plastic track has the characteristics of less dust, good shock absorption and good friction.
[0003] However, the service life of plastic tracks is usually not long, generally 5 to 8 years, which increases the cost of the plastic track in disguise. In addition, slips and falls are prone to occur during exercise when used at night, which greatly increases the risk of accidents during nighttime exercise. Therefore, this article introduces an anti-aging plastic track material with fluorescent ability. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-aging plastic track material and a preparation method thereof to solve the problems existing in the prior art.
[0005] An anti-aging plastic runway material, which is prepared by reacting isophorone diisocyanate, 1,3-propylenediamine and modified polysiloxane, and then mixing, coating and drying with a crown ether polymer and a zinc acetate solution;
[0006] The crown ether polymer is prepared by reacting vinyl chloride with methyl phosphine and dibenzo-18-crown-6-ether in sequence;
[0007] The modified polysiloxane is prepared by reacting aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane and 3-aminopropylmethyldimethoxysilane;
[0008] The anti-aging siloxane is prepared by reacting 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol with 3-chloropropyldimethoxymethylsilane;
[0009] The modified siloxane is prepared by reacting 3-aminopropylmethyldimethoxysilane with salicylaldehyde.
[0010] A method for preparing an anti-aging plastic track material, the method for preparing the anti-aging plastic track material mainly comprises the following preparation steps:
[0011] (1) 2 parts of vinyl chloride, 1 part of methyl phosphine, 8-10 parts of ethylene dichloride, 0.8-0.9 parts of dibenzo-18-crown-6-ether and 1.1-1.2 parts of a catalyst are taken in molar proportions, the vinyl chloride and methyl phosphine are mixed, placed in a high-pressure reactor, reacted at 115-125° C. for 10-12 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and a catalyst are added, stirred at 70-90° C. and 200-300 r / min for 22-26 hours, cooled to room temperature, filtered, washed with methanol 3-5 times, and vacuum dried at -10-0° C. for 22-26 hours to obtain a crown ether polymer;
[0012] (2) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and a hydrochloric acid solution with a mass fraction of 36-38% are stirred at 200-300 r / min for 2.5-3.5 hours, the water layer is removed, and vacuum drying is performed at -10-0°C for 22-26 hours to obtain a modified polysiloxane;
[0013] (3) Mix isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide in a mass ratio of 2-2.4:2-3:0.01:0.6-0.8:16-20, stir at 70-90°C, under nitrogen protection, at 200-300 r / min for 4-6 hours, add crown ether polymer with a mass of 0.3-0.5 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.4-0.6 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate, continue stirring for 3-5 minutes, apply it on the surface of the substrate, and dry it at 70-90°C for 7-9 hours to obtain a plastic track material.
[0014] As an optimization, the catalyst in step (1) is ferric chloride.
[0015] As an optimization, the modified siloxane in step (2) is prepared by mixing 3-aminopropylmethyldimethoxysilane, salicylaldehyde and methanol in a molar ratio of 1:1:8-10, stirring at 50-70°C and 200-300 r / min for 3-5 hours, cooling to room temperature, and vacuum drying at -10-0°C for 22-26 hours.
[0016] As an optimization, the aging-resistant siloxane in step (2) is prepared by mixing 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol, acetonitrile and 3-chloropropyldimethoxymethylsilane in a molar ratio of 1:10 to 12:1, stirring at 200 to 300 r / min for 14 to 18 hours, and vacuum drying at -10 to 0°C for 22 to 26 hours.
[0017] As an optimization, the zinc acetate solution in step (3) is prepared by uniformly mixing zinc acetate and methanol in a mass ratio of 1:20 to 30.
[0018] As an optimization, the specific operation method of the washing in step (3) is to wash with methanol 3 to 5 times.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] When preparing the anti-aging plastic track material, the present invention sequentially reacts vinyl chloride with methylphosphine and dibenzo-18-crown-6-ether to obtain a crown ether polymer; reacts 3-aminopropylmethyldimethoxysilane with salicylaldehyde to obtain a modified siloxane; reacts 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol with 3-chloropropyldimethoxymethylsilane to obtain an anti-aging siloxane; reacts the anti-aging siloxane, the modified siloxane, dimethyldimethoxysilane and 3-aminopropylmethyldimethoxysilane to obtain a modified polysiloxane; reacts isophorone diisocyanate, 1,3-propylenediamine and the modified polysiloxane, and then mixes with the crown ether polymer and a zinc acetate solution, applies the mixture and dries the mixture to obtain the anti-aging plastic track material.
[0021] First, vinyl chloride is reacted with methyl phosphine and dibenzo-18-crown-6-ether in sequence to obtain a crown ether polymer; organic phosphorus can react chemically with active free radicals generated during the combustion process, thereby inhibiting the generation and conduction of free radicals and preventing effective contact between oxygen and the burning material, which can reduce the activity of the surface of the burning material, slow down the formation of flames and the rate of the combustion reaction, thereby playing a flame retardant role. At the same time, organic phosphorus can also release a large amount of phosphorus-containing compounds during the combustion process. These compounds can generate phosphates with carbon on the surface of the burning material at high temperature to form a phosphate protective layer, which covers the surface of the burning material and plays a role of heat insulation and oxygen isolation, preventing the burning material from continuing to burn, thereby improving the flame retardant ability of the material; there is a host-guest effect between the crown ether and the quaternary ammonium salt on the subsequent polysiloxane, which can achieve a self-healing effect at room temperature.
[0022] Secondly, 3-aminopropylmethyldimethoxysilane is reacted with salicylaldehyde to obtain modified siloxane; 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol is reacted with 3-chloropropyldimethoxymethylsilane to obtain anti-aging siloxane; anti-aging siloxane, modified siloxane, dimethyldimethoxysilane and 3-aminopropylmethyldimethoxysilane are reacted to obtain modified polysiloxane; isophorone diisocyanate, 1,3-propylenediamine and modified polysiloxane are reacted and then mixed with crown ether polymer and zinc acetate solution, coated and dried to obtain anti-aging plastic track material; quaternary ammonium salt and hindered phenol bond are loaded on polysiloxane; Under the action of heat, light and oxygen, organic molecules will break at the weakest chemical bonds to generate active free radicals. Hindered phenol antioxidants, as a free radical capture antioxidant, can prevent further degradation of organic molecules by capturing these free radicals; the steric hindrance groups in hindered phenol antioxidant molecules can also shield the formed phenoxy free radicals, preventing the formation of new oxidation cycles, thereby improving aging resistance; when the Schiff base zinc complex is excited by external energy, the substance will release radiation energy when it is deactivated from the excited state to the low-energy state with the same multiplicity, which is fluorescence, making it convenient for night use. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0026] (1) 2 parts of vinyl chloride, 1 part of methylphosphine, 8 parts of ethylene dichloride, 0.8 parts of dibenzo-18-crown-6-ether and 1.1 parts of a catalyst are taken in molar proportions, the vinyl chloride and methylphosphine are mixed, placed in a high-pressure reactor, reacted at 115° C. for 10 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and the catalyst are added, stirred at 70° C. and 200 r / min for 22 hours, cooled to room temperature, filtered, washed with methanol 3 times, and vacuum dried at -10° C. for 22 hours to obtain a crown ether polymer;
[0027] (2) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 36% hydrochloric acid solution were stirred at 200 r / min for 2.5 h in a mass ratio of 1:1:5:0.3:5:8, the water layer was removed, and the mixture was vacuum dried at -10°C for 22 h to obtain modified polysiloxane;
[0028] (3) Mix isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide in a mass ratio of 2:2:0.01:0.6:16, stir at 70°C under nitrogen protection at 200 r / min for 4 h, add crown ether polymer with a mass of 0.3 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.4 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate, continue stirring for 3 min, cure in a mold, and dry at 70°C for 7 h to obtain a plastic track material.
[0029] Example 2
[0030] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0031] (1) 2 parts of vinyl chloride, 1 part of methylphosphine, 9 parts of ethylene dichloride, 0.85 parts of dibenzo-18-crown-6-ether and 1.15 parts of a catalyst are taken in molar proportions, the vinyl chloride and methylphosphine are mixed, placed in an autoclave, reacted at 120° C. for 11 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and the catalyst are added, stirred at 80° C. and 250 r / min for 24 hours, cooled to room temperature, filtered, washed with methanol 4 times, and vacuum dried at -5° C. for 24 hours to obtain a crown ether polymer;
[0032] (2) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were stirred at 250 r / min for 3 h in a mass ratio of 1:1:6:0.35:6:9, the water layer was removed, and the mixture was vacuum dried at -5°C for 24 h to obtain modified polysiloxane;
[0033] (3) Isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide were mixed in a mass ratio of 2.2:2.5:0.01:0.7:18, stirred at 80°C under nitrogen protection at 250 r / min for 5 h, crown ether polymer with a mass of 0.4 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.5 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate were added, stirring was continued for 4 min, the mixture was cured in a mold, and dried at 80°C for 8 h to obtain a plastic track material.
[0034] Example 3
[0035] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0036] (1) 2 parts of vinyl chloride, 1 part of methylphosphine, 10 parts of ethylene dichloride, 0.9 parts of dibenzo-18-crown-6-ether and 1.2 parts of a catalyst are taken in molar proportions, the vinyl chloride and methylphosphine are mixed, placed in a high-pressure reactor, reacted at 125° C. for 12 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and the catalyst are added, stirred at 90° C. and 300 r / min for 26 hours, cooled to room temperature, filtered, washed with methanol 5 times, and vacuum dried at 0° C. for 26 hours to obtain a crown ether polymer;
[0037] (2) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 38% hydrochloric acid solution were stirred at 300 r / min for 3.5 h in a mass ratio of 1:1:7:0.4:7:10, the water layer was removed, and the mixture was vacuum dried at 0°C for 26 h to obtain modified polysiloxane;
[0038] (3) Mix isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide in a mass ratio of 2.4:3:0.01:0.8:20, stir at 90°C under nitrogen protection at 300 r / min for 6 h, add crown ether polymer with a mass of 0.5 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.6 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate, continue stirring for 5 min, cure in a mold, and dry at 90°C for 9 h to obtain a plastic track material.
[0039] Comparative Example 1
[0040] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0041] (1) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were stirred at 250 r / min for 3 h in a mass ratio of 1:1:6:0.35:6:9, the water layer was removed, and the mixture was vacuum dried at -5°C for 24 h to obtain modified polysiloxane;
[0042] (2) Mix isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide in a mass ratio of 2.2:2.5:0.01:0.7:18, stir at 80°C under nitrogen protection at 250 r / min for 5 h, add dibenzo-18-crown-6-ether (0.4 times the mass of isophorone diisocyanate), zinc acetate solution (0.5 times the mass of isophorone diisocyanate) and acetone (equal to the mass of isophorone diisocyanate), continue stirring for 4 min, cure in a mold, and dry at 80°C for 8 h to obtain a plastic track material.
[0043] Comparative Example 2
[0044] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0045] (1) 2 parts of vinyl chloride and 1 part of methyl phosphine are mixed by mole, placed in a high-pressure reactor, reacted at 120° C. for 11 hours, and then taken out to obtain a flame retardant;
[0046] (2) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were stirred at 250 r / min for 3 h in a mass ratio of 1:1:6:0.35:6:9, the water layer was removed, and the mixture was vacuum dried at -5°C for 24 h to obtain modified polysiloxane;
[0047] (3) Mix isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide in a mass ratio of 2.2:2.5:0.01:0.7:18, stir at 80°C, under nitrogen protection, at 250 r / min for 5 h, add a flame retardant with a mass of 0.4 times that of isophorone diisocyanate, a zinc acetate solution with a mass of 0.5 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate, continue stirring for 4 min, cure in a mold, and dry at 80°C for 8 h to obtain a plastic track material.
[0048] Comparative Example 3
[0049] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0050] (1) 2 parts of vinyl chloride, 1 part of methyl phosphine, 9 parts of ethylene dichloride, 0.85 parts of dibenzo-18-crown-6-ether and 1.15 parts of a catalyst are taken in molar proportions, the vinyl chloride and methyl phosphine are mixed, placed in an autoclave, reacted at 120° C. for 11 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and the catalyst are added, stirred at 80° C. and 300 r / min for 24 hours, cooled to room temperature, filtered, washed with methanol 4 times, and vacuum dried at -5° C. for 24 hours to obtain a crown ether polymer;
[0051] (2) Modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were stirred at 250 r / min for 3 h in a mass ratio of 1:6:0.35:6:9, the water layer was removed, and the mixture was vacuum dried at -5°C for 24 h to obtain modified polysiloxane;
[0052] (3) Isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide were mixed in a mass ratio of 2.2:2.5:0.01:0.7:18, stirred at 80°C under nitrogen protection at 250 r / min for 5 h, crown ether polymer with a mass of 0.4 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.5 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate were added, stirring was continued for 4 min, the mixture was cured in a mold, and dried at 80°C for 8 h to obtain a plastic track material.
[0053] Comparative Example 4
[0054] An anti-aging plastic track material and a preparation method thereof, mainly comprising the following preparation steps:
[0055] (1) 2 parts of vinyl chloride, 1 part of methylphosphine, 9 parts of ethylene dichloride, 0.85 parts of dibenzo-18-crown-6-ether and 1.15 parts of a catalyst are taken in molar proportions, the vinyl chloride and methylphosphine are mixed, placed in an autoclave, reacted at 120° C. for 11 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and the catalyst are added, stirred at 80° C. and 250 r / min for 24 hours, cooled to room temperature, filtered, washed with methanol 4 times, and vacuum dried at -5° C. for 24 hours to obtain a crown ether polymer;
[0056] (2) Aging-resistant siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were stirred at 250 r / min for 3 h in a mass ratio of 1:6:0.35:6:9, the water layer was removed, and the mixture was vacuum dried at -5°C for 24 h to obtain modified polysiloxane;
[0057] (3) Isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide were mixed in a mass ratio of 2.2:2.5:0.01:0.7:18, stirred at 80°C under nitrogen protection at 250 r / min for 5 h, crown ether polymer with a mass of 0.4 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.5 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate were added, stirring was continued for 4 min, the mixture was cured in a mold, and dried at 80°C for 8 h to obtain a plastic track material.
[0058] Test Example 1
[0059] Flame retardant test
[0060] The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.
[0061] Table 1
[0062] Limiting oxygen index Example 1 28.8% Example 2 29.1% Example 3 28.9% Comparative Example 1 23.1% Comparative Example 2 28.7% Comparative Example 3 29.0% Comparative Example 4 28.8%
[0063] From the comparison of the experimental data in Table 1, it can be found that the anti-aging plastic track material prepared by the present invention has good flame retardancy.
[0064] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is higher than that of Comparative Example 1, which shows that the organic phosphorus can react chemically with the active free radicals generated in the combustion process, thereby inhibiting the generation and conduction of free radicals and preventing effective contact between oxygen and the combustion material, which can reduce the activity of the surface of the combustion material, slow down the formation of flames and the rate of combustion reaction, thereby playing a flame retardant role. At the same time, the organic phosphorus can also release a large amount of phosphorus-containing compounds during the combustion process. These compounds can generate phosphates with carbon on the surface of the combustion material at high temperature to form a phosphate protective layer, which covers the surface of the combustion material and plays a role of heat insulation and oxygen isolation, preventing the combustion material from continuing to burn, thereby improving the flame retardant ability of the material.
[0065] Test Example 2
[0066] Self-repair and aging resistance test
[0067] Self-repair test method: The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were made into strips with a length of 10 mm, a width of 4 mm, and a thickness of 1 mm, and the tensile performance was tested. The tensile fracture strength was tested at 5 mm / min. A small cut of 2 mm in length and 0.5 mm in depth was made transversely on the same sample, and the sample was left to stand at room temperature for 24 hours. The tensile fracture strength was tested again, and the repair efficiency was calculated, wherein the repair efficiency = tensile fracture strength after self-repair / tensile fracture strength before self-repair * 100%;
[0068] Aging resistance test method: The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were made into strips with a length of 10 mm, a width of 4 mm, and a thickness of 1 mm, and the tensile properties were tested. The tensile breaking strength was tested at 5 mm / min. The same samples were irradiated under a fluorescent ultraviolet lamp UV-A340 for 15 days, and the tensile breaking strength was tested. The tensile breaking retention rate was calculated, where the tensile breaking retention rate = tensile breaking strength after aging / tensile breaking strength before aging * 100%. The results are shown in Table 2.
[0069] Table 2
[0070] Repair efficiency Tensile break retention rate Example 1 95.9% 97.9% Example 2 96.3% 98.2% Example 3 96.0% 98.3% Comparative Example 1 96.2% 98.0% Comparative Example 2 63.5% 97.8% Comparative Example 3 63.1% 95.1% Comparative Example 4 96.1% 98.2%
[0071] From the comparison of the experimental data in Table 2, it can be found that the anti-aging plastic track material prepared by the present invention has good self-repair and aging resistance capabilities.
[0072] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 2, it can be found that the repair efficiency of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which shows that there is a host-guest effect between the crown ether and the quaternary ammonium salt, and the self-repair effect can be achieved at room temperature;
[0073] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 2, it can be found that the tensile fracture retention rates of Examples 1, 2, 3 are higher than those of Comparative Example 3, which indicates that under the action of heat, light and oxygen, organic molecules will break at the weakest chemical bonds to generate active free radicals. Hindered phenol antioxidants, as a free radical capture antioxidant, can prevent further degradation of organic molecules by capturing these free radicals; the steric hindrance groups in the hindered phenol antioxidant molecules can also shield the formed phenoxy free radicals, preventing the formation of new oxidation cycles, thereby improving aging resistance.
[0074] Test Example 3
[0075] Fluorescence test
[0076] Test method: The test was conducted using a steady-state / transient fluorescence spectrometer at a wavelength of 430 to 450 nm. The results are shown in Table 3.
[0077] Table 3
[0078] Fluorescence Example 1 Blue fluorescence Example 2 Blue fluorescence Example 3 Blue fluorescence Comparative Example 1 Blue fluorescence Comparative Example 2 Blue fluorescence Comparative Example 3 Blue fluorescence Comparative Example 4 No fluorescence
[0079] From the comparison of the experimental data in Table 3, it can be found that the anti-aging plastic track material prepared by the present invention has fluorescence ability.
[0080] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 3, it can be found that Examples 1, 2, 3 have fluorescence compared with Comparative Example 4, which shows that when the Schiff base zinc complex is excited by external energy, the substance deactivates from the excited state to the low-energy state with the same multiplicity and releases radiation energy, that is, fluorescence.
[0081] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An anti-aging plastic track material, characterized in that: The anti-aging plastic track material is prepared by reacting isophorone diisocyanate, 1,3-propylenediamine and modified polysiloxane, and then mixing, coating and drying with a crown ether polymer and a zinc acetate solution; The crown ether polymer is prepared by reacting vinyl chloride with methyl phosphine and dibenzo-18-crown-6-ether in sequence; The modified polysiloxane is prepared by reacting aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane and 3-aminopropylmethyldimethoxysilane; The anti-aging siloxane is prepared by reacting 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol with 3-chloropropyldimethoxymethylsilane; The modified siloxane is prepared by reacting 3-aminopropylmethyldimethoxysilane with salicylaldehyde.
2. A method for preparing an anti-aging plastic track material, characterized in that: The preparation method of the anti-aging plastic track material mainly includes the following preparation steps: (1) 2 parts of vinyl chloride, 1 part of methyl phosphine, 8-10 parts of ethylene dichloride, 0.8-0.9 parts of dibenzo-18-crown-6-ether and 1.1-1.2 parts of a catalyst are taken in molar proportions, the vinyl chloride and methyl phosphine are mixed, placed in a high-pressure reactor, reacted at 115-125° C. for 10-12 hours, taken out, and under nitrogen protection, ethylene dichloride, dibenzo-18-crown-6-ether and a catalyst are added, stirred at 70-90° C. and 200-300 r / min for 22-26 hours, cooled to room temperature, filtered, washed with methanol 3-5 times, and vacuum dried at -10-0° C. for 22-26 hours to obtain a crown ether polymer; (2) Aging-resistant siloxane, modified siloxane, dimethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, deionized water and a hydrochloric acid solution with a mass fraction of 36-38% are stirred at 200-300 r / min for 2.5-3.5 hours, the water layer is removed, and vacuum drying is performed at -10-0°C for 22-26 hours to obtain a modified polysiloxane; (3) Mix isophorone diisocyanate, 1,3-propylenediamine, dibutyltin dilaurate, modified polysiloxane and N,N-dimethylformamide in a mass ratio of 2-2.4:2-3:0.01:0.6-0.8:16-20, stir at 70-90°C, under nitrogen protection, at 200-300 r / min for 4-6 hours, add crown ether polymer with a mass of 0.3-0.5 times that of isophorone diisocyanate, zinc acetate solution with a mass of 0.4-0.6 times that of isophorone diisocyanate and acetone with a mass equal to that of isophorone diisocyanate, continue stirring for 3-5 minutes, apply it on the surface of the substrate, and dry it at 70-90°C for 7-9 hours to obtain a plastic track material.
3. The method for preparing an anti-aging plastic track material according to claim 2, characterized in that: The catalyst in step (1) is ferric chloride.
4. The method for preparing an anti-aging plastic track material according to claim 2, characterized in that: The modified siloxane in step (2) is prepared by mixing 3-aminopropylmethyldimethoxysilane, salicylaldehyde and methanol in a molar ratio of 1:1:8-10, stirring at 50-70°C and 200-300 r / min for 3-5 hours, cooling to room temperature, and vacuum drying at -10-0°C for 22-26 hours.
5. The method for preparing an anti-aging plastic track material according to claim 2, characterized in that: The aging-resistant siloxane in step (2) is prepared by mixing 2,6-di-tert-butyl-p-(dimethylaminomethyl)phenol, acetonitrile and 3-chloropropyldimethoxymethylsilane in a molar ratio of 1:10 to 12:1, stirring at 200 to 300 r / min for 14 to 18 hours, and vacuum drying at -10 to 0°C for 22 to 26 hours.
6. The method for preparing an anti-aging plastic track material according to claim 2, characterized in that: The zinc acetate solution in step (3) is prepared by uniformly mixing zinc acetate and methanol in a mass ratio of 1:20 to 30.
7. The method for preparing an anti-aging plastic track material according to claim 2, characterized in that: The specific operation method of the washing in step (3) is to wash with methanol 3 to 5 times.